Application Integration : EAI B2B BPM and SOA. - Manouvrier, Bernard (John Wiley & Sons, 2008)
Application integration assembles methods and tools for organizing exchanges between applications, and intra- and inter-enterprise business processes. A strategic tool for enterprises, it introduces genuine reactivity into information systems facing business changes, and as a result, provides a significant edge in optimizing costs. This book analyzes various aspects of application integration, providing a guide to the alphabet soup behind EAI, A2A, B2B, BAM, BPM, ESB and SOA. It addresses the problems of choosing between the application integration solutions and deploying them successfully. It.